Alterations in foot positioning during ankle taping and its effects on range of motion and jump performance in dancers - Anderson, E.; Stanek, J.; McLoda, T.; Jagodinsky, A.; Heiman, B. (International Journal of Athletic Therapy & Training, 2025)
A closed basketweave ankle tape application is common throughout sports, yet less prevalent in the performing arts. This may be due to aesthetics and potential compromises to performance. The purpose of this study was to examine the effects of foot positioning (dorsiflexed or neutral/resting) during tape application on static range of motion (ROM), kinematic ROM, and jump ability while performing a maximum sauté jump. A randomized crossover cohort study design was used to evaluate ankle active ROM, kinematic ROM, and ground reaction force during a dance bipedal vertical jump. Results showed the application of tape caused significant differences in active ROM when compared with the no-tape condition. No significant differences in ground reaction force were found and inconsistent kinematic changes were found from the peak ROM data. Foot position during ankle taping does not appear to affect jump performance but does show similar active ROM restrictions, particularly in plantarflexion and inversion.